Performance of widely held and cross holding firms in Malaysia - Nallamuthu, Balamurugan (2013)
This study investigates the relationship between widely held firms (WH) and cross holding firms (CH) and their performance in an area which to the researcher’s knowledge has not been studied before in Malaysia. WH firms are classified as public listed firms where individual shareholdings do not exceed 20% whereas CH firms are public listed entities with more than 20% ownership by another public listed firm. This study adopted the expected performance model created by Barber and Lyon in 1996 to determine the performance of the two types of firms. Thus, this research developed the expected performance models of the firms and compared them with actual and not past performance as extensively used in prior studies. To derive accurate industry comparisons, sample firms are re-categorized according to the Malaysia Standard Industrial Classification 2008 (MSIC, 2008). Prior studies used the Bursa Malaysia industry classification to compare the performance of firms against the industry. This study is based on panel data for 16 WH firms, 21 CH firms and 163 industry benchmark firms in Malaysia for the period 2004 to 2011. The main objectives of the study are to compare the abnormal performance of WH and CH firms and to determine the relationship between abnormal performance and the two types of firms. Abnormal return on assets (ABROA) and abnormal return on sales (ABROS) were used to measure their performance. Based on ABROA and ABROS,the findings of the study show that the performance of CH firms to be superior to WH firms. This was confirmed by an independent means test. For the relationship between CH ownership and abnormal performance, statistical tests show that CH firms positively related to both ABROA and ABROS, although the latter is not significantly related to their performance. In contrast, widely held firms are negatively related to abnormal performance. Here too ABROS is not statistically significant in explaining the relationship. This study also noted that leverage as a control variable negatively related to abnormal performance regardless of the ownership type. This is consistent with previous studies conducted on firms in Malaysia and other parts of the world. Performance is positively related to the age of firms in both categories with older firms managing their assets more efficiently to create better results. On an overall basis, in Malaysia the performance of CH firms is better than that of WH firms and the CH firm shows positive relationship with performance and WH is negatively related with performance.